Inter-firm rivalry and firm growth: Is there any evidence of direct competition between firms? - Alex Coad; Mercedes Teruel (Max Planck Institute of Economics, 2010)
Inter-firm competition has received much attention in the theoretical literature, but recent empirical work suggests that the growth rates of rival firms are uncorrelated, and that firm growth can be taken as an essentially independent process. We begin by investigating the correlations of the growth rates of competing firms (i.e. the largest and second-largest firms in the same industry) and observe that, surprisingly, the growth of these firms can be taken as independent. Nevertheless, peer-effect regressions, that take into account the simultaneous interdependence of growth rates of rival firms, are able to identify significant negative effects of rivals' growth on a firm's growth.
urn:nbn:de:gbv:27-20110628-151526-4
Keywords: L25; 330; Competition; Firm growth; Peer effects econometrics; Unternehmenswachstum; Wettbewerb; Soziale Gruppe; Schätzung; Spanien